The Effect Of Four-Goal Soccer Training On The Ability Of Passing-Stopping Basic Movements - Jackson Sijabat; Dicky Hendrawan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
The purpose of this study was to determine the effect of four-goal football training on the ability of basic movements of passing-stopping in the game of football for male students of class VII SMP Swasta Persiapan Serdang. This research is an experimental study with a One Group Pretest and Posttest design or the absence of a control group. The One Group Pretest and Posttest Design method is a research design with a pretest before being given treatment, thus the treatment results can be known more accurately because they can compare with the situation before being given treatment. So that the series in this research design is that there is an initial test or what is called a pretest to determine the initial ability of students to do passing-stopping, then given treatment, namely with a four-goal soccer game and ends with a final test or posttest to determine the results of the passing-stopping test after being given treatment. Based on the results of research that has been obtained by analyzing data and testing hypotheses, it can be concluded that there is a significant effect of 17.14% Four-goal football training on the ability of basic movements of passing-stopping in soccer games for male students of Class VII SMP Swasta Persiapan Serdang.